Pasangan Ideal dalam Kehidupan Rumah Tangga Masa Kini: Kajian Dhou'ul Misbah Fi Bayani Ahkam An-Nikah - Muhammad Fatih (PROGRESSA: Journal of Islamic Religious Instruction, 2022)
Spouses play a crucial role in achieving a harmonious marriage and establishing a happy and prosperous family. Choosing the right partner is key to the success of a marriage. The book Dhou’ul Misbah fi Bayani Ahkamin Nikah, written by Sheikh Muhammad Hasyim Asy’ari, discusses the views on the criteria for an ideal spouse as a husband and wife, as well as its relevance in contemporary family life. This research falls under the category of literature research that utilizes data from literary sources. The primary data consists of the book Dhou’ul Misbah fi Bayani Ahkamin Nikah by Sheikh Muhammad Hasyim Asy’ari, while the secondary data includes literature such as yellow books, books, journal articles, and others related to the research theme. The method used is descriptive-analytical. The author will describe Sheikh Muhammad Hasyim Asy’ari's thoughts on the criteria for an ideal spouse as stated in the book Dhou’ul Misbah fi Bayani Ahkamin Nikah, and then analyze its relevance in contemporary family life. In conclusion, the criteria for an ideal spouse described in Sheikh Muhammad Hasyim Asy’ari's work are highly relevant as guidelines in choosing a husband or wife, especially in the current digital era filled with sexual temptations and materialism.